Negatifikasi Kapitalisasi: Kajian Terhadap Pa’pandan Sebagai Fenomena Pemberian dalam Konteks Budaya Toraja - Tendenan, Vani (Theologia in Loco, 2023)
Pa’pandan is a practice of gift-giving in the Toraja culture of South Sulawesi. The article identifies that pa’pandan has become a harmful practice because of the influence of capitalization. The practice is embedded in the debt system affecting mainly the less fortunate people in the Torajan society. This article focuses on efforts to negate cultural capitalization that influences the practice of pa’pandan to become an uncontrolled or excessive gift-giving practice. As a result, it produces gifts that have a negative impact. Bringing Jean Luc-Marion’s phenomenological method into dialogue with the negative theology according to Arthur Bradley, this article offers a negative theological view on a gift-giving practice to reconstruct the practice of pa’pandan into becoming a more effective practice with a more positive impact, especially in transforming the debt system in the life of the marginalized.